Review of the merger between Klein Karoo International (Pty) Ltd, Mosstrich (Pty) Ltd and Cape Karoo (Pty) Ltd: an application of the Guppi and Upp tests - Siyo, Zintle (My University, 2021)
This research paper reviews the merger between Klein Karoo International (Pty) Ltd (“KKI”), Mosstrich (Pty) Ltd (“Mosstrich”) and Cape Karoo (Pty) Ltd (“Ostrich merger”). The Ostrich merger was prohibited by the Competition Commission (Commission). Upon review, the Competition Tribunal (Tribunal) approved the merger subject to conditions. This paper focuses on the meat market as the Ostrich case's main contention was the meat market. In reviewing the Ostrich merger, this research paper applies two price pressure indices, the Upward Pricing Pressure (UPP) and Gross Upward Pricing Pressure Index (GUPPI). The two indices are computed and used as alternative screening tools to analyse the horizontal merger, involving differentiated products in an oligopoly market. The computed indices are analysed based on two different scenarios. The first scenario relies on the Commission's market definition, while the second uses the merging parties' description of the market. The results indicate that both UPP and GUPPI, under the two different scenarios, show that the merger would have created incentives to raise prices
A research report submitted to the School of Economics and Finance, Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the degree of Master of Commerce (Economics), 2021